Vocational Education in Volyn Province during the Second Polish Republic - Волонтир О. (Видавничо-поліграфічний центр "Київський університет", 2017)
The article studies the main trends in the development of vocational education in the Second Polish republic. The reasons that prompted the Polish government not to ignore this sphere and simultaneously start its reforming are considered. The peculiarities of the regulatory framework and regulatory acts on professional and technical education in the 1920s and 1930s were revealed. The structure, peculiarities of the functioning of specialized educational institutions, as well as the educational process, the main motives of teaching and the training of the teaching staff, are analyzed, respectively. The main content of the policy of the Polish government in Volyn of the interwar period regarding the vocational training is highlighted. The role of the educational reform of 1932 in the creation of an integrated system of vocational and technical education in the then Polish country was revealed. The place of the professional school in the educational system of the Second Polish republic has been clarified. The regional peculiarities and significance of professional education of cultural and educational development of local population are revealed. Areas of vocational education are highlighted and an attempt is made to study the direction of the content of the educational process in educational institutions of this type in the territory of the Volyn province.

У статті досліджуються головні тенденції розвитку професійно-технічної освіти у Другій Речі Посполитій. Розглянуто причини, що спонукали польський уряд не залишати поза увагою цю сферу та водночас розпочати її реформування. Виявлено особливості нормативно-правової бази та регуляторних актів щодо професійної та технічної освіти у 1920-х і 1930-х рр. Проаналізовано структуру, особливості функціонування спеціалізованих навчальних закладів, а також показано навчальний процес, основні мотиви викладання та стан підготовки викладацького складу відповідно. Висвітлено головний зміст політики польського уряду на Волині міжвоєнного періоду стосовно професійно-технічного навчання. Розкрито роль освітньої реформи 1932 р. у створенні комплексної системи професійної та технічної освіти в тогочасній польській країні. З'ясовано місце професійної школи в освітній системі Другої Речі Посполитої. Виявлено регіональні особливості та значимість професійної освіти для культурно-освітнього розвитку місцевого населення. Виділено напрями професійної освіти та зроблено спробу дослідження спрямованості змісту виховного процесу в навчальних закладах такого типу на території Волинського воєводства.
Професійно-технічна освіта у Волинському воєводстві за часів Другої Речі Посполитої
Keywords: vocational education; the Second Polish republic; Volyn province; професійно-технічна освіта; Друга Річ Посполита; Волинське воєводство